COMPENSATORY GROWTH AND FAT PARAMETERS ON BROILER FASTED IN EARLY LIFE - Sugiharto, S.; Henckel, P.; Lauridsen, L. (Diponegoro University, 2010)
The experiment was carried out to investigate the effect of feed withholding in the very early life ofbird on its compensatory growth capacity and fat parameters. A total of 60 mixed-sexes of one day oldRoss chicks were used in the experiment conducted with completely randomized design of 2 differentfeeding times after hatching, i.e.: T1: given access to feed and water ad libitum immediately afterhatching until 35d of age; and T2: withheld from feed (fasted) but not from water for 48h after hatchingand then fed ad libitum until d35. The birds were weighed at the start of experiment and weeklythereafter, and DWG was then calculated. Feed intakes and FCR were also recorded weekly. At d36,abdominal fat was taken out from 2 birds per pen and was weighed. Breast meat (skinless) from thesame birds was also sampled for total FA analysis. Final BW (d35) and total feed consumption of earlyfastedbirds were 1935.17±43.90 kg and 2745.55±47.48 kg and those of unfasted birds were2019.00±50.85 kg and 2910.84±128.10 kg, respectively. FCR of early-fasted and unfasted birds at d35were 1.42±0.03 and 1.45±0.07. The magnitude difference of DWG between early-fasted and unfastedbirds was 27% at d7, whereas at d35 the difference was only 4.5%. Abdominal fat percentage to live BWof early-fasted birds was 1.65±0.09% (male) and 1.60±0.10% (female) and that of unfasted birds was2.00±0.19% (male) and 1.89±0.38% (female). Total FA contained in meat of early-fasted and unfastedbirds were 0.82±0.10 and 0.85±0.10 g/100gDM. Overall, BW and feed consumption of early-fastedbirds were significantly lower (P<0.05) than unfasted birds. DWG, FCR, abdominal fat and total FAcontained in meat were not significantly different (P>0.05) between early-fasted and unfasted birds. Inconclusion, holding birds without feed following hatch (under practical conditions) may limit thecompensatory growth capacity of birds in the later age. Fasting applied in the very early life of broilerleads to impairment of cell hyperplasia resulting in permanent stunting. Abdominal fat and total FAcontained in meat might not be affected by fasting for 48h after hatching. The degree or duration of feedwithholding (for 48h after hatching) might not sufficient to reduce adipocyte proliferation or the numberof precursor adipocytes.